Microencapsulation of Peumus boldus essential oil and its impact on peanut seed quality preservation - Girardi, Natalia Soledad (2018)
Argentinean peanut provides a significant source of food worldwide, therefore is essential to preserve the quality of seeds during the storage period in order to ensure the yield of this crop. In this study in situ effect of a formulation based on microencapsulated boldo (Peumus boldus) essential oil (EO) was evaluated on in-pod stored peanut (Arachis hipogaea) to preserve the seed quality. Statistically significant (p < 0.05) fungitoxic effects were observed at the end of the storage period. Seed damages caused by insects was very low during the 5 months, however, reductions of seed germinations were produced by the formulation. Low levels of residual boldo oil were recorded at the end of the assay. The application of boldo oil microcapsules is useful to preserve stored peanuts avoiding its deterioration, but not when it is intended for seed, but for another purposes as by-product elaboration.